Effect of the Histone Methyltransferase Specific Probe BRD4770 on Metabolic Profiling of the Endophytic Fungus Diaporthe longicolla - Nishad, Jay Hind; Singh, Arti; Bharti, Rajnish; Prajapati, Priyanka; Sharma, Vijay Kumar; Gupta, Vijai Kumar; Kharwar, Ravindra Nath (Frontiers in Microbiology, 2021)
The endophytic fungus Diaporthe longicolla was isolated from the stem of Saraca asoca (Roxb.) Willd., commonly known as Ashok plant in India and Srilanka. Since no reports are available regarding epigenetic modulations by BRD4770 in microbial entities, hence D. longicolla was treated with different concentrations of BRD4770 for this purpose and evaluated for its antioxidant and antibacterial potential against five human pathogenic bacteria Staphylococcus aureus, Methicillin-resistant Staphylococcus aureus (MRSA), Shigella boydii, Klebsiella pneumoniae and Escherichia coli. The crude extract obtained from cultures treated with 100nM concentration of BRD4770, showed increased antioxidant activity and inhibition zone against S. aureus and MRSA, compared to the non-treated control. The composition of non-treated as well as treated crude extract were analyzed and induced compounds were identified with the help of GC-MS and LC-ESI-MS/MS. LC-ESI-MS/MS analysis showed berberine (antibacterial), caffeine and theobromine (antioxidant) like compounds etc. were induced in BRD4770 treated crude extract. The presence of particular absorbance at wavelength 346.5 for berberine, 259.4 for caffeine, and 278.4nm for theobromine in the reverse phase HPLC analysis of both BRD4770 treated crude metabolites and standard solution of above compounds strongly supported the increased antibacterial and antioxidant activities that may be due to inducing the alterations in bioactivities of BRD4770 treated culture.